Experimental Determination of Melting Rates of Ice Moving in Seawater. - Clifford,William Francis; Erman,Reginald Joseph (1979)
Large, fresh-water ice blocks (0.5m x 1.25 x 5m) were towed in Monterey Bay at speeds in range from 0.7 to 1.2 knots. Experimental objectives included measuring gross regression rates of ice surfaces, wake temperature, turbulent thermal boundary layer, ice interior temperature profile, and observation of shape changes over the melting period. The research was conducted over a period from Oct 1977 to January 1979. Measured regression rates at several points on the ice blocks were compared to theoretical predictions using a turbulent flow ice ablation model developed by Owen Griffin of the Naval Research Lab. Griffin's model predicted a regression rate of 280mm/hr compared with the measured value of 260mm/hr at a selected point. Temperature profiles in the ice interior and ice-water boundary layer were used in a one-dimensional energy balance across the melting interface. Ice ripples, observed on all ice block tests, are important for both heat transfer and drag considerations. Wavelengths of the ripples were measured and the average wavelength was 6.1 in. compared to the theoretical average predicted by Tatinclaux and Kennedy of 5.8 in. for a selected experiment.